Training needs of smes Bagaces city - Bermúdez Carrillo, Luis Alberto (2015)
When the needs of Small and Medium enterprises ( SMEs ) are mentioned often think of that have to do with financing as low, however, deficiencies or other limitations may constitute key factors that prevent them to develop their potential a convenient and accurate way. Under this concept, the present study aims to identify the training needs with SMEs Bagaces city as priority. Due to its characteristics, this research is descriptive and is based on the opinions of a sample of 98 entrepreneurs to whom they were given a survey to find out their views. In general, according to the results of this survey, the largest number of identified training needs have to do with legal and tax support, management models and organizational development, technological and structural aspects of nature.